The role of acetogens in microbially influenced corrosion of steel - Mand, Jaspreet; Park, Hyung Soo; Jack, Thomas R.; Voordouw, Gerrit (Frontiers in Microbiology, 2014)
Microbially-influenced corrosion (MIC) of iron (Fe0) by sulfate reducing bacteria (SRB) has been studied extensively. Through a mechanism, that is still poorly understood, electrons or hydrogen (H2) molecules are removed from the metal surface and used as electron donor for sulfate reduction. The resulting ferrous ions precipitate in part with the sulfide produced, forming characteristic black iron sulfide. Hydrogenotrophic methanogens can also contribute to MIC. Incubation of pipeline water samples, containing bicarbonate and some sulfate, in serum bottles with steel coupons and a headspace of 10% (vol/vol) CO2 and 90% N2, indicated formation of acetate and methane. Incubation of these samples in serum bottles, containing medium with coupons and bicarbonate but no sulfate, also indicated that formation of acetate preceded the formation of methane. Microbial community analyses of these enrichments indicated the presence of Acetobacterium, as well we of hydrogenotrophic and acetotrophic methanogens. The formation of acetate by homoacetogens, such as Acetobacterium woodii from H2 (or Fe0) and CO2, is potentially important, because acetate is a required carbon source for many SRB growing with H2 and sulfate. A consortium of the SRB Desulfovibrio vulgaris Hildenborough and A. woodii was able to grow in defined medium with H2, CO2 and sulfate, because A. woodii provides the acetate, needed by D. vulgaris under these conditions. Likewise, general corrosion rates of metal coupons incubated with D. vulgaris in the presence of acetate or in the presence of A. woodii were higher than in the absence of acetate or A. woodii, respectively. An extended MIC model capturing these results is presented.